Aggregation of Star Polymers: Complexation versus Segregation. Issue 6 (30th July 2018) - Hebbeker, Pascal; Plamper, Felix A.; Schneider, Stefanie
Abstract: Complex‐forming copolymers (polymers whose monomeric units of different type attract each other) are often discussed to be a pathway to achieve self‐assembled structures, which differ from the classical micellization scheme. Here, coarse‐grained Monte Carlo simulations are performed to investigate the aggregation behavior of miktoarm star polymers/diblock copolymers, which are able to form complexes between the constitutional blocks. These results are compared with the corresponding polymers without complexation, but allowing segregation of one of the blocks (selective solvent scenario). By analyzing the radial distribution function and the effective polymer–polymer interaction the occurrence of aggregates is probed. While the segregating copolymers form larger aggregates, the complex‐forming copolymers are stable against aggregation up to concentrations in the order of the overlap concentration. These results are in line with former experimental findings. Abstract : The aggregation behavior of complex forming miktoarm star polymers is investigated using coarse‐grained Monte Carlo simulations. It is shown that miktoarm star polymers which form intramolecular complexes are not prone to intermolecular aggregation. This behavior is explained using the effective interaction between the star polymers and the results are compared with segregating star polymers.